Home Gardening and Food Security Concerns during the COVID-19 Pandemic - Maja Turnšek; Siv-Lene Gangenes Skar; Marit Piirman; Ragnheiður I. Thorarinsdottir; Martina Bavec; Ranka Junge (Horticulturae, 2022)
At times of crisis, home gardening has often been sought out as a potential solution for threats to food security and as a measure to increase socio-psychological effects, such as public sense of self-efficacy, trust in the government and care for one’s wellbeing. The objective of this study was to investigate if home gardening increased during the COVID-19 pandemic in the spring/summer of 2020 and to provide socio-psychological insights into the explanatory factors of such an increase. An explanatory theoretical model of home gardening was proposed and tested to analyse whether home gardening is correlated to food security concerns, and if so, to what extent. A non-representative survey was conducted in five European countries (Slovenia, Norway, Estonia, Switzerland, and Iceland) using snowball sampling via social media networks, reaching 1144 participants. The results showed the pandemic did prove to be an important psychological push towards home gardening prompted by food security concerns. Measured as loose as introducing at least one new gardening activity during COVID-19, this study found an approximately 10% increase in home gardening during the first wave of COVID-19 in the sample population, which was skewed towards educated, female, middle-class Europeans.